Investigation of the association between allergic rhinitis and pathological weight gain in school-age children in Samara - O. V. Skvortsova; N. B. Migacheva; E. G. Mikhaylova (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2023)
.